Development of LKPD with a Contextual Approach Based on Flipbook to Increase Science Learning Motivation - Dwi Agnes Setianingrum*; El Minahussaniyyatul Ula; Septania Pratiwi; Jumadi Jumadi (Jurnal Pendidikan Sains Indonesia, 2022)
The science learning process at SMP N 1 Pejagoan is still teacher-centered. This causes students to be less active because the control of learning is centered on the teacher, as a result, students' learning motivation decreases. To overcome this, research was carried out through the development of study guides in the form of LKPD with a contextual approach based on flipbook. This study aims to determine the feasibility level of LKPD, determine student responses, and find out whether LKPD can increase students' motivation to learn science. This study uses the Thiagarajan 4D (Four-D Model) development model, consisting of four stages, namely the definition stage, the design stage, and the development stage. The dissemination stage was not carried out, this research was only limited to product feasibility tests and limited trials. This study uses a descriptive qualitative approach. The sample in this study is class VIII A totaling 10 people. The collection technique used is a questionnaire and documentation. The results showed that: (1) LKPD with a contextual approach based on flipbook was feasible, judging from the percentage of LKPD eligibility 95.57% (very feasible), (2) student responses to LKPD were in the very good category, seen from the percentage of interest in LKPD 87.50% (very interested), and students' motivation to learn science using LKPD with a contextual approach based on flipbook was included in the high category, with a percentage of 82.81% (high motivation)